Streaming and the Online Hong Kong Underground: Conversations with Two Hong Kong Improvised Music Actors - Mouillot, François (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This essay takes the form of a patchwork of conversations with Hong Kong-based organizers and improvisers Dennis 'Sin:Ned' Wong and Steve ‘Nerve’ Hui to address the differences in conditions and implications of livestreaming for improvising musicians/’noisicians’ in the Hong Kong experimental music scene. Questions that formed the basis for discussion in these conversations include: How does online gigging in the era of the Covid pandemic extend pre-existing activities of the Hong Kong improvised music communities? What are the social, aesthetic, and operational impact of the digital 'platforming' on their musical activities? What is the potential for these online tools to generate deep-rooted and longer-lasting connections either between musicians, and/or musicians and audiences/other scene actors?